2016
DOI: 10.1002/cne.24051
|View full text |Cite
|
Sign up to set email alerts
|

Expression of homeobox genes in the mouse olfactory epithelium

Abstract: Homeobox genes constitute a large family of genes widely studied because of their role in the establishment of the body pattern. However, they are also involved in many other events during development and adulthood. The main olfactory epithelium (MOE) is an excellent model to study neurogenesis in the adult nervous system. Analyses of homeobox genes during development show that some of these genes are involved in the formation and establishment of cell diversity in the MOE. Moreover, the mechanisms of expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 101 publications
1
14
0
Order By: Relevance
“…This indicates that alternative processes likely mediate the enhanced social memory consequent to Meis1 deficiency. Recent evidence showing zonal Meis1 expression in the main olfactory epithelium could signify one potential avenue for further investigation in this regard ( Parrilla et al, 2016 ). Furthermore, in light of this new evidence, a more detailed analysis of cognitive ability in RLS patients with the MEIS1 risk haplotype is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that alternative processes likely mediate the enhanced social memory consequent to Meis1 deficiency. Recent evidence showing zonal Meis1 expression in the main olfactory epithelium could signify one potential avenue for further investigation in this regard ( Parrilla et al, 2016 ). Furthermore, in light of this new evidence, a more detailed analysis of cognitive ability in RLS patients with the MEIS1 risk haplotype is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The riboprobes applied for P2ry13 were F: ACAGACAACATCACCCTAGCCT, R: CCT CTCTTCTGGTGCTCTGTTT (corresponding to nucleotide positions 1055-1663 [accession number NM_028808.3, available from Allen Bain Atlas] 1 and for Cx3cr1 F: GACGATT CTGCTGAGGCCTGTTA, R: CCTCGCTTGTGTAGTGAGTG AAAC (corresponding to nucleotide position 147-1143) [accession number NM_028808.3]). Riboprobes were designed and synthesized as previously described (Ishii et al, 2004 ; Parrilla et al, 2016 ) using hippocampus cDNA as a template. Single- or two-color FISH combined with immunohistochemistry was performed as described (Ishii et al, 2004 ) with slight modifications: (1) hybridization step: slices were incubated in 12 μg/ml of proteinase K solution at 37°C for 16 min; (2) hybridization of P2ry13 and Cx3cr1 riboprobes labeled with digoxigenin and fluorescein, respectively, was performed at 65°C overnight in the hybridization solution (Parrilla et al, 2016 ); and (3) detection step: antibodies against digoxigenin-alkaline phosphatase (11093274910, Roche) and fluorescein horseradish peroxidase (NEF710, PerkinElmer) were incubated together with the following primary antibodies: anti-Iba1, anti-GFAP, anti-SRY (sex determining region Y)-box 2 (Sox2; Sc-17320, 1:200, Santa Cruz), anti-DCX, anti-NeuN (ABN78, 1:500, Millipore), anti-somatostatin (AB5494, 1:200, Millipore) and/or anti-parvalbumin (PV27, 1:200, Swant).…”
Section: Methodsmentioning
confidence: 99%
“…Single- or two-color FISH combined with immunohistochemistry was performed as described (Ishii et al, 2004 ) with slight modifications: (1) hybridization step: slices were incubated in 12 μg/ml of proteinase K solution at 37°C for 16 min; (2) hybridization of P2ry13 and Cx3cr1 riboprobes labeled with digoxigenin and fluorescein, respectively, was performed at 65°C overnight in the hybridization solution (Parrilla et al, 2016 ); and (3) detection step: antibodies against digoxigenin-alkaline phosphatase (11093274910, Roche) and fluorescein horseradish peroxidase (NEF710, PerkinElmer) were incubated together with the following primary antibodies: anti-Iba1, anti-GFAP, anti-SRY (sex determining region Y)-box 2 (Sox2; Sc-17320, 1:200, Santa Cruz), anti-DCX, anti-NeuN (ABN78, 1:500, Millipore), anti-somatostatin (AB5494, 1:200, Millipore) and/or anti-parvalbumin (PV27, 1:200, Swant). Signals of digoxigenin and fluorescein probes were detected as described (Parrilla et al, 2016 ). Primary antibodies were detected with Alexa Fluor 488-coupled donkey anti-mouse (A21202, 1:500), donkey anti-rat (A21208, 1:500) or Alexa Fluor 647-coupled donkey anti-rabbit (A31573, 1:250) or donkey anti-goat (A21447, 1:250) secondary antibodies (all from Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated that many Prep1 co-factors, belonging to TALE family, are highly abundant in mouse olfactory bulbs and play key roles in olfactory interneurons’ regeneration from SVZ neuroblasts [ 21 , 22 ]. Therefore, the marked expression of Prep1 in olfactory bulb might suggest a key biological function of this transcription factor in olfactory sensory circuit or olfactory renewal processes, which are inevitably related.…”
Section: Discussionmentioning
confidence: 99%
“…However, Prep1 plays also a central function in the early and late stages of rodent brain development, by forming binary and ternary complexes with other homeodomain factors, such as Pbx1, Hoxb1, and Meis [ 15 19 ]. Stable expression and activity of these Prep1 co-factors, however, have been detected also in many regions of adult brain, especially in olfactory sensory areas [ 20 22 ]. In silico gene expression data, reported on Bio-GPS® ( http://biogps.org/#goto=genereport&id=18771 ) and Allen Brain® ( http://mouse.brain-map.org/gene/show/18535 ) web-based atlases, show that Prep1 is widely expressed in several regions of adult mouse brain but in particular within the olfactory bulb.…”
Section: Introductionmentioning
confidence: 99%